Outcomes Associated With Osteochondral Allograft Transplantation in Dogs - Franklin, Samuel P.; Stoker, Aaron M.; Murphy, Sean M.; Kowaleski, Michael P.; Gillick, Mitchell; Kim, Stanley E.; Karlin, Michael; Cross, Alan; Cook, James L. (Frontiers in Veterinary Science, 2021)
The purpose of this study was to retrospectively characterize outcomes and complications associated with osteochondral allograft transplantation for treating chondral and osteochondral lesions in a group of client-owned dogs with naturally-occurring disease. Records were reviewed for information on signalment, treated joint, underlying pathology (e.g. osteochondritis dissecans; OCD), and type, size, and number of grafts used. Complications were classified as “trivial” if no treatment was provided, “non-surgical” if non-surgical treatment were needed, “minor surgical” if a minor surgical procedure such as pin removal were needed but the graft survived and function was acceptable, or “major” if the graft failed and revision surgery were needed. Outcomes were classified as unacceptable, acceptable, or full function. Thirty-five joints in 33 dogs were treated including nine stifles with lateral femoral condyle (LFC) OCD and 10 stifles with medial femoral condyle (MFC) OCD treated with osteochondral cylinders or “plugs”. There were 16 “complex” procedures of the shoulder, elbow, hip, stifle, and tarsus using custom-cut grafts. In total there were eight trivial complications, one non-surgical complication, two minor surgical complications, and five major complications for a total of 16/35 cases with complications. Accordingly, there were five cases with unacceptable outcomes, all of whom had major complications while the other 30 cases had successful outcomes. Of the 30 cases with successful outcomes, 15 had full function and 15 had acceptable function. Based on these subjective outcome assessments, it appears osteochondral allograft transplantation is a viable treatment option in dogs with focal or complex cartilage defects. However, no conclusions can be made regarding the inferiority or superiority of allograft transplantation in comparison to other treatment options based upon these data.